Bioethanol: Renewable energy source - Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
According to the official document of Romania's energy policy for the period 2020-2030, with a view to 2050, the main objective of the strategy is to increase the energy sector in conditions of sustainability by setting targets for reducing greenhouse gas emissions and promoting renewable energy. In Romania, due to the specifics of each geographical area and environmental restrictions, production systems can be developed by types of renewable sources. The paper presents the importance of using renewable energy for bioethanol production as well as a SWOT analysis to highlight strengths, weaknesses, opportunities and threats regarding bioethanol production in Romania. This type of analysis is useful for decision makers as well as those involved in the value chain for obtaining bioethanol. Considered the most widespread biofuel, bioethanol is a renewable energy source with multiple benefits. The main resources used to obtain bioethanol come from starch raw materials (corn, wheat, potatoes, cassava) to which are added lignocellulosic raw materials in the form of agricultural waste (cereal straw, sugar cane waste, fiber and cotton waste). Renewables currently have a relatively small share in the structure of energy sources in the EU. This requires the promotion of the renewables sector: from legislation to the integration of technologies and the support of innovation in this field.
Keywords: Q2; Q20; Q28; 330; energy policy; renewable energy sources; biofuels; bioethanol